Towards Broadcasting Linear Content Over 5G Network - Shurdi, Olimpjon; Lala, Algenti (European Scientific Journal, ESJ, 2023)
Today’s society heavily relies on linear television systems featuring planned programs, which serve as a vital means of communication. The evolution of broadcasting linear content is notably driven by advancements in end users’ devices. This transition has expanded it from a limited range of linear radio and TV channels to a comprehensive and distinctive array. This selection is accessible across diverse distribution network types. Among these networks, the prominence of the 5G network stands out as a notable platform for media and transmissions. Transmitting linear content over 5G networks involves efficiently delivering scheduled, real-time content to a large number of users simultaneously. This content encompasses live TV broadcasts, radio programs, and streaming events. While 5G networks offer significant advantages in capacity, speed, and latency, it’s essential to consider specific factors when it comes to broadcasting linear content. Traditionally, cellular networks, designed for continuous service, have predominantly followed a unicast bidirectional communication paradigm for numerous years, providing a range of services to customers. This paper employs a research methodology to examine the future 3rd Generation Partnership Project (3GPP) 5G Multicast and Broadcast Services (MBS) standards, along with their constraints. Our approach includes a comprehensive literature review, technical specification analysis, and comparison of different broadcasting technologies within the 5G framework. By employing this research methodology, we gain a holistic understanding of the evolving landscape of broadcasting linear content over 5G networks. This contributes to the body of knowledge in this field and informs future advancements in broadcast technologies within the 5G ecosystem.